STUDY ON PATHOGEN OF LUMINOUS DISEASE VIBRIO HARVEYI ON LARVAE AND JUVENILE OF MUD CRAB (SCYLLA SERRATA) IN HATCHERY - Muu, Tran The; Sang, Vu Van (Vietnam Journal of Marine Science and Technology, 2016)
Luminous disease is known as the most popularly dangerous disease in the hatcheries of mud crab (Scylla serrata) in northern provinces. Without any treatment, the mortality caused by this disease may reach 50 - 100% after 2 - 3 days infected. In this study, Vibrio harveyi has been identified as the main pathogen which causes the disease in larvae and juvenile of mud crab by using method for bacteria identification (bio-chemical reaction and comparision of the gene 16S rDNA) as well as artificial disease infection. In addition, we have developed successful prevention and treatment for this disease as follows: potasium permanganate, chlorine, formaline used for treatment of water, crab spawners, living food (artemia), utensils and equipment, after that one of the three different kinds of antibiotics can be used: Neomycine, Erythromycine or Doxycyclin. For prevention, the dose of 2 ppm/day can be applied for 3 consecutive beginning days of each development stage (Zoea, Megalope and juvenile), and 3 ppm/day can be applied for 3 consecutive days for disease treatment.